Ganarse la vida en los parques. Apropiación del espacio público durante la pandemia Covid-19 - Merino Solari, Renatto (2022)
This article seeks to understand two aspects related to the occupation of public space in the context of the pandemic. The first seeks to identify the uses and appropriations that people make of parks, while the second seeks to explore the use of parks as a means of earning a living. For this, the dynamics of five parks located in the district of San Miguel in metropolitan Lima were observed. Through an ethnographic research, it was concluded that the main form of appropriations is the transformations of parks into productive territories. Formally conceived as recreational settings for natural and aesthetic enjoyment, they became spaces for work and survival (material and subjective) that allowed people to make a living in a context of a deep employment crisis.